General anaesthesia during infancy reduces white matter micro-organisation in developing rhesus monkeys. (April 2021) - Young, Jeffrey T.; Vlasova, Roza M.; Howell, Brittany R.; Knickmeyer, Rebecca C.; Morin, Elyse; Kuitchoua, Kaela I.; Lubach, Gabriele R.; Noel, Jean; Hu, Xiaoping; Shi, Yundi; Caudill, Gibson; Alexander, Andrew L.; et al.
Abstract: Background: Non-human primates are commonly used in neuroimaging research for which general anaesthesia or sedation is typically required for data acquisition. In this analysis, the cumulative effects of exposure to ketamine, Telazol® (tiletamine and zolazepam), and the inhaled anaesthetic isoflurane on early brain development were evaluated in two independent cohorts of typically developing rhesus macaques. Methods: Diffusion MRI scans were analysed from 43 rhesus macaques (20 females and 23 males) at either 12 or 18 months of age from two separate primate colonies. Results: Significant, widespread reductions in fractional anisotropy with corresponding increased axial, mean, and radial diffusivity were observed across the brain as a result of repeated anaesthesia exposures. These effects were dose dependent and remained after accounting for age and sex at time of exposure in a generalised linear model. Decreases of up to 40% in fractional anisotropy were detected in some brain regions. Conclusions: Multiple exposures to commonly used anaesthetics were associated with marked changes in white matter microstructure. This study is amongst the first to examine clinically relevant anaesthesia exposures on the developing primate brain. It will be important to examine if, or to what degree, the maturing brain can recover from these white matter changes.